(3GSJOQGc GHf GdNTGH Ydi GdMQjQj aj ebGeGJg hGSJOQGc GHf HQj Ydjg ajeG GSJOQcg hGfJUGQg ddMQjQjs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s ((3eMeO Hf YHOGdedc GHf YSGcQ GdTGaYj GdHYdHcj s)
(3ChdgG (B:s
(3hHYO(B: (3agPg MQha hbYJ aj GdebGeGJ GdJj CfSCgG CHheMeO GdbGSe Hf Ydj GdHUQj GdMQjQj fHg YdjgG GdTjN CHhYHOGddg s
(3BNQgG (B:s
"(3aSbW GdaJi aj jOg(B" (3hBNQ eG LGA aj HjGf gPG GdNWC hgh VejQ GdfOe Ydi eG Hjf Cgd GdYQHjI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B154 - (3U(B177s
(3gfGc Tc aj GSe GdfGSNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B23 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs